The knowledge level and practices on childhood injuries and interventions among parents at home (Bangladesh Journal of Medical Science, 2022)
Background: There are many common household emergencies that may involve children. This includes poisoning, falls, burns, choking, animal bites, very high fever and also febrile fits. Knowledge about preventive measures to prevent these accidents as home as well as knowing what to do when it occurs may help in preventing further complications and may aid in recovery. Therefore, this study aims to find out the general public knowledge regarding the preventive steps and early emergency steps that can be taken upon emergencies occurring among children.Methods: A cross sectional study incorporating a questionnaire/instrument that included brief sociodemographic data and a total of 10 questions on common household injuries and emergencies, and either preventive steps or early interventions was used. The topics covered were 6 core topics on poisoning, falls, burns, choking, animal bites, high fever and also febrile fits.Results: The total number of respondents was 119 parents. This study overall showed a good knowledge, attitude and practice among the parents towards common emergency inflicting children. Older aged and female parent were found to have more knowledge and positive attitude towards common emergencies among children, respectively.Conclusion: Group identified as having a lower knowledge, attitude and/or practice should be targeted in future community education programmes to increase the knowledge as well positive attitudes and practices towards identifying and managing common emergencies among children.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 140-144